A STUDY OF THE BED HEIGHT IN A TWO-PHASE FLUIDIZATION: NUMERICAL SIMULATION AND STATISTICAL ANALYSIS - Nu'man Fadhilah Rudiawan, Aufa
At present, the design and scale-up of fluidization reactor rely on the empirical process, where the fundamental knowledge about fluid-particle interaction and particle-particle interaction is still limited. Laboratory-scale experiment must take place, even though they are time-consuming and sometimes very expensive. Numerical simulation can aid this problem, such as molecular dynamics method. Fluid and particle phase were governed by the discrete model and fluid-particle interaction were determined by the collision between particles. Statistical analysis can be useful too, such as multiple linear regression method. The hydrodynamics behavior of fluidization are predicted through relation between variables. This Thesis consist of numerical simulation and statistical analysis to observe the bed height in a two-phase fluidization. Two-phase fluidization are consist of gas fluidization (gas-solid) and liquid fluidization (liquid-solid). Numerical simulation result shows that bed height increase for zeolite sand at fluid velocity 3.200 m/s, alumina and active sand at fluid velocity 6.400 m/s, and silica sand at fluid velocity 8.000 m/s at gas fluidization. At liquid fluidization, bed height increase for zeolite sand at fluid velocity 2 m/s, alumina and active sand at fliuid velocity 8 m/s, and silica sand at fluid velocity 10 m/s. Statistical analysis result shows that at gas fluidization, the bed height are affected by initial height and spherisity and at liquid fluidization, the bed height are affected by initial height, diameter, spherisity, and density.